2016
DOI: 10.1158/1078-0432.ccr-15-0603
|View full text |Cite
|
Sign up to set email alerts
|

EphA2 Expression Is a Key Driver of Migration and Invasion and a Poor Prognostic Marker in Colorectal Cancer

Abstract: Purpose: EphA2, a member of the Eph receptor tyrosine kinases family, is an important regulator of tumor initiation, neovascularization, and metastasis in a wide range of epithelial and mesenchymal cancers; however, its role in colorectal cancer recurrence and progression is unclear.Experimental Design: EphA2 expression was determined by immunohistochemistry in stage II/III colorectal tumors (N ¼ 338), and findings correlated with clinical outcome. The correlation between EphA2 expression and stem cell markers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
119
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(129 citation statements)
references
References 47 publications
6
119
2
Order By: Relevance
“…The higher EphB4 expression in colon cancer compared to normal mucosa was previously shown at the mRNA level in 62 tissue pairs, with validation at the protein level in only a few samples [14]. Although we did not find a significant correlation between EphA2 or EphB4 expression and the stage or differentiation grade of the tumors, earlier studies found both EphA2 and EphB4 to be preferentially up-regulated in the early cancer stages (stages I and II) [5][6][7][8][9]15]. Over-expression in early colorectal cancer stages is particularly advantageous for imaging during surgery, given the increased difficulty in distinguishing normal and tumor tissue morphologically and the fact that for early stage tumors surgery is often not accompanied by chemotherapy.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The higher EphB4 expression in colon cancer compared to normal mucosa was previously shown at the mRNA level in 62 tissue pairs, with validation at the protein level in only a few samples [14]. Although we did not find a significant correlation between EphA2 or EphB4 expression and the stage or differentiation grade of the tumors, earlier studies found both EphA2 and EphB4 to be preferentially up-regulated in the early cancer stages (stages I and II) [5][6][7][8][9]15]. Over-expression in early colorectal cancer stages is particularly advantageous for imaging during surgery, given the increased difficulty in distinguishing normal and tumor tissue morphologically and the fact that for early stage tumors surgery is often not accompanied by chemotherapy.…”
Section: Discussioncontrasting
confidence: 57%
“…Multiple publications have shown that EphA2 overexpression is strongly correlated with tumor progression, and consequently high EphA2 levels are associated with worse patient survival [8,13,16]. High EphB4 expression has also been correlated with poor patient survival [17][18][19], although some studies have also found an opposite correlation [15].…”
Section: Discussionmentioning
confidence: 99%
“…These data collectively challenge the general assumption that tumors classified as mesenchymal, or in the CMS4 subgroup, have undergone widespread EMT, resulting in lower levels of epithelial-associated traits in the tumor cell compartment, when actually these tumors have a higher component of stromal (particularly fibroblast) infiltration. Although IHC-based analysis of colorectal cancer tumors has shown that neoplastic epithelial cells expressing stem-like properties have a poor prognosis (15)(16)(17), our findings emphasize that the CMS4 subgroup represents tumors with higher transcription levels of mesenchymal-associated genes, which can be attributed to their overall stromal-rich, and in particular fibroblast, architecture.…”
Section: Discussionmentioning
confidence: 56%
“…64) Dunne et al found that EphA2 Ser-897 and EphA2 Tyr-772 as well as total EphA2 were upregulated in an invasive colorectal cancer cell line harboring the KRAS active mutation. 42) Of note, the stem cell markers CD44 and Lgr5 also were increased in these cells, suggesting EphA2 Ser-897 may be involved in cancer stemness. De Robertis et al reported that colon adenocarcinoma cells with high EphA2 expression levels isolated from the AOM/DSS mouse model showed higher levels of stem cell markers and lower levels of differentiation markers than the low-EphA2 population.…”
Section: Cell Survival and Proliferationmentioning
confidence: 91%
“…41) Many reports showed that patients with low ephrin-A1 expression had a poor prognosis, suggesting the existence of EphA2 tyrosine kinase-independent regulation. 31,42,43) Thirty-seven phosphorylation sites are identified within the intracellular domain of EphA2 in the PhosphoSitePlus database. 44) Among them, 25 phosphorylation sites are serine and threonine residues.…”
Section: Epha2 Noncanonical Signaling Transductionmentioning
confidence: 99%